Post void residue in women with pelvic organ prolapse: a prospective observational study - Saravanan, Nanthini; Kekre, Aruna N.; S., Mahasampath Gowri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of the present study was to observe the post void residual volume (PVRV) in women with pelvic organ prolapse (POP) pre and postoperatively and to correlate stage of prolapse with lower urinary tract symptoms and quality of life in women with pelvic organ prolapse. Methods: This is a prospective observational cohort study of 100 women with symptomatic pelvic organ prolapse of stage II or greater. Patients were admitted for Vaginal hysterectomy with pelvic floor repair for pelvic organ prolapse in Gynaecology Department at Christian Medical College Hospital, Vellore, India over one year were recruited. This study was approved by the institutional review board and ethical committee of the hospital. Pre- and post-operative PVR were measured. The statistical analysis was done by using SPSS version 21 and P value < 0.05 was considered as statistically significant. Results: In this study 100 patients were recruited and 11% of women had pre-operative high post void residual volume of more than 100 ml. Stages of POP did not correlate with severity of LUTS and QOL. Pre-operative elevated PVR resolved post operatively in 91%, the P value <0.000 which was highly significant. Conclusions: 11% of women had preoperative high PVR. Stages of POP did not correlate with severity of lower urinary tract symptoms (LUTS) and quality of life(QOL). Pre-operative elevated PVR resolved post operatively in 91%, the P value < 0.000 which was highly significant. Majority of the patient with severe pelvic organ prolapse had elevated pre-op PVR which resolved post- operatively after surgical correction.